2015
DOI: 10.4314/sajas.v44i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic acid supplementation on antioxidant capacity and immune responses of broilers challenged orally with <i>Salmonella enterica</i> subsp. <i>enterica Typhimurium</i>

Abstract: Four commercial organic acids and a reference antibiotic, Neoxyval, were administered to commercial broilers to evaluate the efficacy of these products during pre-and post-challenge with Salmonella enterica subsp. enterica Typhimurium (S. Typhimurium) on selected indicators of their antioxidant status and immune responses in serum. Two hundred and eight broilers received one of the following seven treatments: positive control group (CTL+); negative control (CTL−); antibiotic Neoxyval, (NEOX); Gallimix (GALI); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The TAC precisely measures the antioxidant status of any organism (Erel 2004). The body usually keeps a balance between the production of free radicals and antioxidants; however, under stress conditions, the balance shifts towards free radicals and oxidative stress is developed, which may harm cellular machinery, enzymes and DNA and protein (Abudabos & Al-Mufarrej 2014). In the present study, no significant effect was observed by the treatments on TBARS concentration during the two weeks, however, at the end of the study, TAC decreased significantly in the infected group and infected groups treated with organic acid and probiotic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TAC precisely measures the antioxidant status of any organism (Erel 2004). The body usually keeps a balance between the production of free radicals and antioxidants; however, under stress conditions, the balance shifts towards free radicals and oxidative stress is developed, which may harm cellular machinery, enzymes and DNA and protein (Abudabos & Al-Mufarrej 2014). In the present study, no significant effect was observed by the treatments on TBARS concentration during the two weeks, however, at the end of the study, TAC decreased significantly in the infected group and infected groups treated with organic acid and probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Improved TAC was also reported in another study in broilers simultaneously challenged with S. enterica subsp. enterica typhimurium and an organic acid (Abudabos & Al-Mufarrej 2014) and/or in response to S. boulardii and B. subtilis B10 (Rajput et al 2013). The probiotic bacteria resist oxidation process, scavenge free radical and enhance the antioxidant potential of the organism (Capcarova et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sangrovit ® (Phytobiotics, Eltville, Germany) is an herbal extract prepared from the plume poppy (Macleaya cordata). Varium TM (Amlan International, Inc., Chicago, USA) is a non-antibiotic promoter and Fysal ® (Selko ® Feed Additives) is formulated from a blend of organic acids and their ammonium salts with a high buffer capacity (Abudabos and Al-Mufarrej, 2014). The oil blend MixOil ® (Animal Wellness Products, NE, USA) is formulated from a mixture of seven plant extracts: eucalyptus (Eucalyptus saligna), garlic (Allium sativum), lemon (Citrus limonium), oregano (Origanum vulgare), rosemary (Rosmarinus officinalis), sweet orange (Citrus aurantium), and thyme (Thymus vulgaris) (Rivaroli et al, 2016).…”
Section: Preparation Of Non-agp Test Productsmentioning
confidence: 99%
“…Specific organic acids reduce the pH of poultry feed and lead to the buffering capacity of feed to control intestinal microbial population (Dhama et al, 2014;Abudabos et al, 2017). Organic acids are among alternative growth promoters that have been used in practice for decades, that have been shown to stimulate growth performance in poultry (Abudabos & Al-Mufarrej, 2014;Sultan et al, 2015), and that provide better intestinal health for birds to obtain maximum absorption of nutrients (Hayat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%